2021
DOI: 10.3897/jhr.85.66544
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biology of four Rhodanthidium species (Hymenoptera, Megachilidae) that nest in snail shells

Abstract: Some species of two tribes (Anthidiini and Osmiini) of the bee family Megachilidae utilize empty gastropod shells as nesting cavities. While snail-nesting Osmiini have been more frequently studied and the nesting biology of several species is well-known, much less is known about the habits of snail-nesting Anthidiini. We collected nests of four species of the genus Rhodanthidium (R. septemdentatum, R. sticticum, R. siculum and R. infuscatum) in the Czech Republic, Slovakia, Catalonia (Spain) and Sicily (Italy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…2020; Hostinska et al. 2021) and have found relatively weak preferences for shell species or size. In the present study, we found considerable size variation in shells from the one snail species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2020; Hostinska et al. 2021) and have found relatively weak preferences for shell species or size. In the present study, we found considerable size variation in shells from the one snail species.…”
Section: Discussionmentioning
confidence: 99%
“…2020; Hostinska et al. 2021). The differences among snail species in size at maturity, shape, and abundance have been implicated as potential factors in shell choice (Heneberg et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The semi‐natural habitats could be also beneficial for the diversity of wild bees by providing more nesting opportunities such as bare ground, shrubs, rocky areas etc. (Hostinská et al, 2021; Hudewenz & Klein, 2013; Scheper et al, 2015), while bees in flower strips might be dependent on nesting opportunities provided by semi‐natural habitats adjacent to the field. In such case, the presence of a diverse landscape in the vicinity of the crops may also enhance the diversity of pollinators in the flower strips (Scheper et al, 2015).…”
Section: Discussionmentioning
confidence: 99%